1987
DOI: 10.1016/0035-9203(87)90379-8
|View full text |Cite
|
Sign up to set email alerts
|

Field and laboratory investigation of Crimean-Congo haemorrhagic fever virus (Nairovirus, family Bunyaviridae) infection in birds

Abstract: In November 1984 a case of Crimean-Congo haemorrhagic fever (CCHF) occurred in a worker who became ill after slaughtering ostriches (Struthio camelus) on a farm near Oudtshoorn in the Cape province of South Africa. The diagnosis was confirmed by isolation of CCHF virus from the patient's serum and by demonstration of a specific antibody response. It was suspected that infection was acquired either by contact with ostrich blood or by inadvertently crushing infected Hyalomma ticks while skinning ostriches. Rever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 11 publications
0
49
0
Order By: Relevance
“…CCHF antibody was not detected by IF in the first sheep that fed 12 male and 9 female H. truncatum, nor was virus isolated from 3 pools of fed male ticks, 9 females after oviposition or 8 pools of larvae derived from these females. The other sheep, which was fed upon by 11 Table 4. Titres ranged from 101 3A45 LD 50/ml, with the overall mean titres in newly emerged adults and fed male ticks being higher than those for engorged larvae and nymphae.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…CCHF antibody was not detected by IF in the first sheep that fed 12 male and 9 female H. truncatum, nor was virus isolated from 3 pools of fed male ticks, 9 females after oviposition or 8 pools of larvae derived from these females. The other sheep, which was fed upon by 11 Table 4. Titres ranged from 101 3A45 LD 50/ml, with the overall mean titres in newly emerged adults and fed male ticks being higher than those for engorged larvae and nymphae.…”
Section: Resultsmentioning
confidence: 99%
“…A large number of vertebrate species have been implicated as potential reservoirs. In southern Africa serological surveys indicate that many wild and domestic animals which act as hosts to infected ticks are susceptible to infection [2,9] and experimental studies have shown that cattle, sheep, scrub hares, guinea fowl, and several wild rodent species develop viraemia when infected [10][11][12][13]. In order to assess the role which viraemic vertebrates play as amplifying hosts of the virus and to relate the results of experimental studies to conditions in the field, it is necessary to obtain information on the threshold levels of viraemia necessary for infection of different tick species.…”
Section: Introductionmentioning
confidence: 99%
“…This conclusion was supported by the only two subsequent studies, as researchers were unable to detect antibodies to CCHFV in 37 different species of wild birds in South Africa (Shepherd et al, 1987a), and could not demonstrate viremia in experimentally inoculated hornbills and starlings, even though H. rufipes larvae feeding on them became infected (Zeller et al, 1994). The potential role of migratory birds in the spread of CCHFV to new geographic areas, through the transport of virus-infected larvae and nymphs, is discussed below.…”
Section: Role Of Birds In the Maintenance And Spread Of Cchfvmentioning
confidence: 93%
“…Little information was available on CCHF infection of birds prior to 1984 when a worker contracted the disease at an ostrich abattoir in Oudtshoorn district, South Africa: limited observations in the former Soviet Union had indicated that passerine birds and domestic chickens were refractory to the virus, although a low prevalence of antibody could be detected in wild birds (Hoogstraal, 1979;Shepherd et al, 1987). Transmission experiments were conducted in domestic chickens and guineafowl, showing that the latter develop a transient viraemia .…”
Section: Epidemiologymentioning
confidence: 99%
“…Subsequently, it was found that a few species of wild birds tested in West Africa failed to develop demonstrable viraemia following experimental infection (Zeller et al, 1994). The study conducted by Shepherd et al, 1987 on free-ranging birds demonstrated that ostriches exhibit a much higher prevalence of infection compared to other birds.…”
Section: Epidemiologymentioning
confidence: 99%